ACTR-62. PHASE I TRIAL OF TG02 PLUS DOSE-DENSE OR METRONOMIC TEMOZOLOMIDE FOR RECURRENT HIGH-GRADE ASTROCYTOMA IN ADULTS. (11th November 2019) - Wu, Jing; Bryla, Christine; Su, Yu-Ting; Grajkowska, Ewa; McCoy, Ann; Boris, Lisa; Antony, Ramya; Garren, Nancy; Siegel, Christine; Cordova, Christine; Aboud, Orwa; Vera, Elizabeth; et al.
Abstract: BACKGROUND: Therapies targeting multiple survival pathways are desirable for high-grade gliomas. TG02 (Zotiraciclib), a CDK9 inhibitor, regulates transcription and metabolism of tumor cells and synergizes with temozolomide. A phase I/II trial was launched to test the TG02/temozolomide combined treatment in recurrent high-grade astrocytomas. Phase I results are reported here. METHODS: Adults with recurrent high-grade astrocytoma, KPS≥60, adequate organ function, < 2 prior relapses were enrolled. Primary endpoint was dose limiting toxicity (DLT) in cycle1 in each arm. Bayesian optimal interval design was employed to determine the maximum tolerated dose (MTD) with the target DLT rate of 35% and the toxicity profile of the combination of TG02 (starting dose 200mg orally on days1, 12, 15, and 26) and temozolomide, either as a dose-dense (DD; 125mg/m2/d, 7on/7off, Arm1) or metronomic (MN; 50mg/m2/d, Arm2) dosing schedule on a 28-day cycle. RESULTS: Thirty-eight patients were evaluable; median age 50.7, KPS 90. Of 18 evaluable patients in Arm1, at TG02 dose-level 200mg, 1/6 had a DLT: Gr3 diarrhea; at dose-level 250mg, 3/12 had DLTs: Gr4 neutropenia for over 5 days, Gr3 elevated ALT, and Gr3 fatigue. Of 20 evaluable patients in Arm2, at TG02 dose-level 200mg, 1/6 had a DLT: recurrent Gr3 neutropenia; at dose-level 250mg, 5/12 had a DLT: Gr3 elevated ALT, Gr3 fatigue, and Gr4 neutropenia; at dose-level 300mg, 1 of 2 had a DLT: Gr4 febrile neutropenia, Gr4 elevated ALT, Gr4 elevated AST. TG02 dose-level of 250mg was declared as the MTD in both Arms. Using the MDASI-BT, patients with high symptom burden had increased symptoms during cycle1 but became stable as they continued treatment. CONCLUSION: The combination of TG02 at the MTD of 250mg with DD or MN temozolomide was tolerated. Cohort expansion continues at the MTD in both arms. Objective responses have been observed, suggesting activity of this regimen and supporting continued investigation.